2020
DOI: 10.1186/s11658-020-00241-w
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor 4A family members: mediators in human disease and autophagy

Abstract: The Nuclear receptor 4A (NR4A) subfamily, which belongs to the nuclear receptor (NR) superfamily, has three members: NR4A1 (Nur77), NR4A2 (Nurr1) and NR4A3 (Nor1). They are gene regulators with broad involvement in various signaling pathways and human disease responses, including autophagy. Here, we provide a concise overview of the current understanding of the role of the NR4A subfamily members in human diseases and review the research into their regulation of cell autophagy. A deeper understanding of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…Of those, 84 genes were annotated with the GO term “ positive regulation of transcription from RNA polymerase II promoter ” which was the most significantly enriched for both stimuli (Tables S2 and S3) . This term contained 47 genes that were co‐induced by formoterol and forskolin including NR4A1 , NR4A2 and NR4A3 (Figure S2C), which encode ligand‐independent transcription factors with pro‐ and anti‐inflammatory activities that depend on cellular context (Chen et al, 2020). Formoterol and forskolin also co‐repressed 37 transcripts that were annotated with the same GO term and included FOS , FOSL1 , JUN and JUNB (Figure S2C), whose products homo‐ and heterodimerize to form variants of the pro‐inflammatory transcription factor, activator protein 1 (Zenz et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those, 84 genes were annotated with the GO term “ positive regulation of transcription from RNA polymerase II promoter ” which was the most significantly enriched for both stimuli (Tables S2 and S3) . This term contained 47 genes that were co‐induced by formoterol and forskolin including NR4A1 , NR4A2 and NR4A3 (Figure S2C), which encode ligand‐independent transcription factors with pro‐ and anti‐inflammatory activities that depend on cellular context (Chen et al, 2020). Formoterol and forskolin also co‐repressed 37 transcripts that were annotated with the same GO term and included FOS , FOSL1 , JUN and JUNB (Figure S2C), whose products homo‐ and heterodimerize to form variants of the pro‐inflammatory transcription factor, activator protein 1 (Zenz et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Solid and dashed diagonal lines represent Deming regression and the line of identity, respectively. The proportional, two-way Venn diagrams presented underneath each x-y plot show the number of genes regulated by formoterol, forskolin and both stimuli that met the criteria for significant regulation context (Chen et al, 2020). Formoterol and forskolin also corepressed 37 transcripts that were annotated with the same GO term and included FOS, FOSL1, JUN and JUNB (Figure S2C), whose products homo-and heterodimerize to form variants of the proinflammatory transcription factor, activator protein 1 (Zenz et al, 2008).…”
Section: Effects Of Formoterol and Forskolin On Global Gene Expressionmentioning
confidence: 99%
“…CD83 being a regulatory molecule [54], with its expression directly modulated by NR4As [55]. Growing evidence support that expression levels of NR4As are affected in pathogenic contexts [56], and synthetic regulation of NR4As expression is currently used for treating patients with certain leukemia/lymphomas [57] and could be envisaged for immunomodulatory purposes. In this view, it has been shown that increasing NR4A1 expression levels lead to diminished MoDC and T-cell activation profiles [58].…”
Section: Discussionmentioning
confidence: 99%
“…The NR4A2 gene plays a critical role in the regulation of dopamine and the growth and preservation of neurons. This gene is expressed in various tissues, including the brain, and has been implicated in several vital biological processes, such as neuron survival, mitochondrial biogenesis, and apoptosis (Chen et al (2020)). When modeled using in silico methods, the knockout of the NR4A2 gene correctly predicts the decrease in BDNF production (Barneda-Zahonero et al (2012)) and the alteration of expression of other genes involved in neurotransmitter metabolism and transport, including dopamine (Jankovic et al (2005); Kadkhodaei et al (2013); Jacobs et al (2009)).…”
Section: Dopamine Transcription: the Role Of The Nr4a2 Genementioning
confidence: 99%